THE RESULTS OF STUDIES TO ESTABLISH THE TREATMENT OF THE ELECTRIC LOCOMOTIVE DS3-001 ON THE RAILWAY NETWORK - Rybkin, V. V.; Taturevych, A. P.; Sova, S. M. (Science and Transport Progress, 2005)
Offers on conditions of the reference of new electric locomotive ДС3-001 on a network of railways submitted.